Biometric and rheologic parameters and qualitative properties of meat from "Sarda" breed pigs: Preliminary results - Porcu S.; Mazzette R.; Manca C.; Decandia M.; Busia G.; Riu G.; Ligios S. (7th International Symposium on the Mediterranean Pig, 2012)
The aim of the present study was to evaluate the impact of different breeding systems on the quality parameters of meat from Sarda pigs. Twelve male pigs, aging 15 months, were subdivided in three groups (A,B,C) homogeneous in number of subjects and mean weight (98.4±13.8 kg). Groups A and B were reared in plein-air and fed with commercial concentrate ad libitum and ground barley (1.8 kg/head/day) respectively. Group C was grazed on pasture and received a daily supplement of 500 g/head/day of barley grain. All the subjects were slaughtered after 7 months. A section between L2 to L5 was used to evaluate the lean, fat, rind, connective and bone yield. Samples of muscles Longissimus dorsi and Psoas major and inner fat were used to determinate colorimetric (CIELab) and rheologic (TPA test: 24h – 7days) parameters. Group A showed highest yields in fat (71.8%) and lowest in connective (1.2%) linked to lowest values in terms of hardness. Group B showed highest yields in lean (41.1%) and connective (2.6%) and lowest in fat (48.9%) linked to highest hardness and lowest springiness values. Group C showed intermediate values in lean (34.6%), fat (55.9%) and connective (1.5%) yields but the samples resulted more firm.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)